2023
DOI: 10.1371/journal.pone.0282944
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fall history and toe grip strength in older adults with knee osteoarthritis in Japan: A cross-sectional study

Abstract: Background Knee osteoarthritis (KOA), one of the most common musculoskeletal diseases in older adults, is associated with a high incidence of falls. Similarly, toe grip strength (TGS) is associated with a history of falls in older adults; however, the relationship between TGS and falls in older adults with KOA who are at risk of falling is not known. Therefore, this study aimed to determine if TGS is associated with a history of falls in older adults with KOA. Methods The study participants, older adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Considering the study by Mawarikado et al. [ 19 ], we can surmise that preoperative falls were influenced by preoperative TGS, whereas postoperative falls were influenced by postoperative TGS. As such, we believe that the impact of TGS on perioperative falls in TKA patients cannot be examined longitudinally; instead, TGS must be evaluated before and after surgery to determine the risk for pre‐ and postoperative fall events, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Considering the study by Mawarikado et al. [ 19 ], we can surmise that preoperative falls were influenced by preoperative TGS, whereas postoperative falls were influenced by postoperative TGS. As such, we believe that the impact of TGS on perioperative falls in TKA patients cannot be examined longitudinally; instead, TGS must be evaluated before and after surgery to determine the risk for pre‐ and postoperative fall events, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…This study takes the first step in demonstrating the significance of evaluating TGS to determine the risk for falls after TKA. Considering our findings suggesting that TGS affects falls before [ 19 ] and after TKA, the next step would be to determine how TGS training affects falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, frailty often presents as a dysregulated immune response, exacerbating physical vulnerabilities such as diminished grip strength, an increased risk of falls, and a reduced healthy lifespan in older adults [ 7 , 8 , 9 , 10 , 11 ]. The dysregulation of CD4 + T cells has been shown to aggravate chronic proinflammatory cytokine production during aging [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toe grip strength (TGS) has recently gained interest, as previous reports have shown that TGS affects falls in patients with knee osteoarthritis (KOA) 7 . Tsuyuguchi et al 8 reported that nursing home residents who received TGS training showed significant improvements in TGS and fall risk scores.…”
Section: Introductionmentioning
confidence: 99%